A Circle Game: Issues in Australian Clinical Legal Education - Jeff Giddings (Legal Education Review)
The general course in Public International Law has not traditionally been considered a “black letter law” subject along the lines of the legislation and case law based domestic law subjects in most Australian Law School curricula. Despite the general acceptance among international law educators that international law is much more than simply a set of rules, teaching methods in the subject, at least in Australia, have rarely focused on the actual practices of international law, particularly the peculiarities of the process of international law making. Indeed, a clinical international legal education program has yet to be developed anywhere in Australia. This lack of attention to teaching about the making of international law poses a particular problem in the area of multilateral treaty making. Treaties are one of the four major formal sources of international law and, increasingly, are seen as the most significant component of the international legal order. An understanding of the principles of treaty law is fundamental to any analysis of the substantive provisions of an individual treaty and therefore indispensable to any student of international law. Yet, the methods and processes by which treaties emerge remains relatively unexplored in the discipline. This can be contrasted with scholarly activity in domestic law where “emergence studies” into national legislation is a thriving field.